Enhancing Environmentally Friendly Creative Economy through Plastic Waste Innovation and Financial Reporting Strengthening at Kenanga Waste Bank, Bogor - Azhar, Zul; Mashadi, Mashadi; Mulyana, Mumuh; Herawati, Heti (Jurnal Abdimas Dedikasi Kesatuan, 2025)
Waste banks have become an essential part of the circular economy and a solution to environmental problems, especially in urban areas. Kenanga Waste Bank in Bogor City has served as a community-based waste management center, but it still faces challenges in product innovation using plastic waste and financial recordkeeping. This community service activity aims to enhance the capacity of waste bank managers and members in developing creative products from plastic waste and strengthening financial reports through simple bookkeeping. The methods used included training, product innovation workshops, transaction recording simulations, and financial reporting assistance. The results showed an increase in members’ skills in processing plastic waste into economically valuable products, as well as a 78% increase in understanding of cash inflow and outflow recording. This activity is expected to strengthen the role of waste banks as drivers of environmentally friendly creative economies